Highly Efficient Photoluminescence and Lasing from Hydroxide Coated Fully Inorganic Perovskite Micro/Nano Rods - Ying, G; Ying, G; Taylor, R; Taylor, R; Jana, A; Park, Y; Park, Y (University of Oxford, 2020)
This is a micro-photoluminescence(micro-PL) based study to investigate the optical property of surface passivation effect with Pb(OH)2 coated CsPbBr3 micro/nano rods and demonstration of stimulated emission from defect states. We also presented a technique with completely separable excitation and collection in a confocal microscopy. In this work, we have supported with data from time-resolved study, time-integrated PL map and scan with either collection/excitation fixed and scanning the other.